(untitled) (International Journal of Nursing Education, 2019)
Aim: The aim of the study was to improve the knowledge regarding hypoglycemia and its management among diabetic patients. Methods and Materials: A quantitative pre experimental one group pre-test post-test design was used to collect data from 60 subjects by convenient sampling technique. Self administered structured knowledge questionnaire were used. The collected data was analyzed by using descriptive and inferential statistics. Results: The Median pre-test score was 13 and Median post-test score was 26. The results revealed that among 60 study participants, majority of the diabetic clients (80%) had good knowledge ,15% had average knowledge and only 5% had poor knowledge regarding hypoglycemia and its management. The structured teaching programme was effective. Conclusion: The finding of the study revealed that there was a significant increase in the post-test knowledge scores after structured teaching programme.